Cell-surface vimentin–positive macrophage-like circulating tumor cells as a novel biomarker of metastatic gastrointestinal stromal tumors. (4th May 2018) - Li, Heming; Meng, Qing H.; Noh, Hyangsoon; Somaiah, Neeta; Torres, Keila E.; Xia, Xueqing; Batth, Izhar S.; Joseph, Cissimol P.; Liu, Mengyuan; Wang, Ruoyu; Li, Shulin
ABSTRACT: The clinical utility of circulating tumor cells (CTCs) has been investigated in numerous publications, but CTCs that express very typical immune cell markers have not been reported. Here we report a novel class of CTCs—CSV-positive macrophage-like CTCs (ML-CTCs). This nomenclature was based on the fact that this class of CTCs can be captured from blood samples of gastrointestinal stromal tumors (GISTs) patients using either the macrophage marker CD68 or our proprietary tumor-specific cell-surface vimentin (CSV) antibody 84–1; likewise, the captured ML-CTCs can be co-stained with both typical macrophage markers (CD14, CD68) and tumor cell markers (DOG-1, C-kit) but not CD45. Patients with metastatic GIST had significantly greater numbers of ML-CTCs than patients with localized GIST or cancer-free blood donors (P<0.0001). Unexpectedly, the classic CSV positive CTCs was abundant in metastatic disease but failed to predict GIST metastasis. Only CSV-positive ML-CTCs was able to serve as a solid and novel biomarker for prediction of metastatic risk in GIST patients.